Modulação gênica dos receptores de prostaglandina E2 em células miometriais e cervicais em partos induzidos com prostaglandinas: estudo in vivo e in vitro - Konopka, Cristine Kolling (2015)
The mechanisms involved in human parturition, and the molecular changes that occur during the transition from pregnancy and birth are not completely elucidated. Endogenous or administered prostaglandins, including the PGE1 and PGE2, are related to contractile activity and cervical ripening, playing an important role on labor. Due to maternal or fetal causes, some pregnancies require labor induction. In many cases, prostaglandins, including Dinoprostone (PGE2) and Misoprostol (PGE1 analog), are used for labor induction. However, the response to labor induction is variable, and the reasons why this occurs are unknown. Once delivery also involves modulation of oxidative metabolism, that can be potentially affected by administered drugs, in the present study, we analyzed prostaglandin E2 receptor (EP1, EP2, EP3 and EP4) gene expression of myometrial and cervical cells, in vivo and in vitro, as well as oxidative markers in myometrial cells exposed in vitro to different concentrations of Misoprostol. In both studies, tissue biopsies were obtained from pregnant women at term. In the in vivo study, from women with spontaneous deliveries or Dinoprostone induced labors, responsive or non-responsive to labor induction, and in the in vitro study, from women with spontaneous and non-spontaneous labors, these induced with misoprostol. Gene expression was analyzed by qtRT-PCR and oxidative biomarkers by spectrophotometric and fluorimetric analysis. The results obtained from the in vivo study showed a concurrent and antagonic regulation of EP1 and EP3 mRNA expression in cervical and myometrial tissues in pregnant women at term in Dinoprostone induced labors. EP1 mRNA was upregulated in the cervical tissue of women who did not respond to Dinoprostone induction. In addition, in the myometrium, significantly higher levels of EP3 mRNA were observed in women treated with Dinoprostone, independent of their responsiveness, indicating a possible regulation of the EP3 gene at a transcriptional level. In vitro analysis revealed that myometrial cells derived from women with spontaneous labors showed greater capacity for misoprostol genomic response, since an overexpression of genes associated with muscle contraction (EP1 and EP3) was observed. In addition, Misoprostol was able to differentially modulate two important oxidative metabolism markers (protein carbonylation and lipid peroxidation). However, this effect was dependent on cells source (whether obtained from spontaneous or non-spontaneous labors) and drug concentration. The results suggest that, in term pregnant women, there is modulation of the PGE2 receptors genes in myometrial and cervical tissues in Dinoprostone or Misoprostol-induced labors, and that the EPs have an important role in the success of spontaneous delivery and in the pharmacological response to PGE1 analog administration. Addicionally, oxidative metabolism also seems to play an important role in the parturition process, requiring further studies to define its real function in this process.